2023
DOI: 10.1080/07853890.2023.2236640
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of the Gustave Roussy immune (GRIm) score in cancer patients: a meta-analysis

Ke-Xin Sun,
Ru-Qin Xu,
Huan Rong
et al.

Abstract: Background The prognostic value of the Gustave Roussy immune (GRIm) score in cancer patients has been widely reported but remains inconsistent. The aim of this study is to systematically investigate the relationship between the GRIm score and survival outcomes in cancer patients. Methods Relevant literature was identified using electronic databases including Web of Science, PubMed, and Embase from the inception to March 2023. The primary endpoints were long-term oncolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…10 Additionally, Zhang et al identified cN stage, tumor diameter, and CEA level as predictive factors for the TNT-induced response. 8 Mounting evidence suggests a link between systemic inflammatory response, malnutrition, and treatment sensitivity, as well as prognosis of various gastrointestinal tumors, such as gastric cancer, 11,12 colorectal cancer, 8,13 liver cancer, 14 pancreatic cancer, 15 and gastrointestinal stromal tumor. 16 Therefore, surveillance of the correlation between nutritionalinflammatory index and TNT-induced tumor regression can aid in the early identification of patients who are unlikely to derive benefits from TNT.…”
Section: Introductionmentioning
confidence: 99%
“…10 Additionally, Zhang et al identified cN stage, tumor diameter, and CEA level as predictive factors for the TNT-induced response. 8 Mounting evidence suggests a link between systemic inflammatory response, malnutrition, and treatment sensitivity, as well as prognosis of various gastrointestinal tumors, such as gastric cancer, 11,12 colorectal cancer, 8,13 liver cancer, 14 pancreatic cancer, 15 and gastrointestinal stromal tumor. 16 Therefore, surveillance of the correlation between nutritionalinflammatory index and TNT-induced tumor regression can aid in the early identification of patients who are unlikely to derive benefits from TNT.…”
Section: Introductionmentioning
confidence: 99%